Raw data for a study investigating sustainable tank construction materials for shrimp aquaculture - Bendag Slim; Justus Liebig University Giessen (My University, 2025)
The dataset contains the raw data from a randomised controlled trial investigating whether wood can serve as a sustainable alternative tank construction material in Pacific white shrimp (PWS) aquaculture. The trial compared the effects of tanks lined with Douglas fir wood, oak wood, and conventional fibreglass reinforced plastic (FRP) on shrimp survival, growth, and feed conversion rates over a 42-day period. The dataset consists of four data sheets S1 to S4: 1. Raw data for water quality parameters (temperature, salinity, nitrite, pH, dissolved oxygen, nitrate, and phosphate) measured weekly in 12 aquaria over the course of the 42-day trial across the three tank material treatments (FRP, Douglas fir, and oak). Named “Table S1: Raw data of the water parameters measured weekly in a 42-day controlled trial investigating the effect of tank material on growth and survival parameters of Pacific white shrimp”. 2. Raw data for growth and feed conversion parameters of Pacific white shrimp (PWS), including initial and final body weight, feed input, mortality, calculated weight gain (%), specific growth rate (% per day), and feed conversion ratio (FCR) per tank for each treatment group. Named “Table S2: Raw data from a 42-day controlled trial investigating the effect of tank material (oak, Douglas fir and fiberglass reinforced plastic (FRP) as control) on growth parameters and survival of Pacific white shrimp. Treatment names correspond to the respective type of material used to cover 60% of the trial aquariums' surface. For figure 2 (A: Survival rate, C: Weight gain, D: Specific growth rate and E: Feed conversion ratio)”. 3. Raw data for survival analysis, including individual survival time (in days), mortality events (1 = death, 0 = survival), and corresponding treatment codes (1 = FRP, 2 = Douglas fir, 3 = oak) for the Kaplan-Meier survival analysis. Named “Table S3: Raw data for Figure 2B and the Kaplan-Meier survival time analysis for a 42-day controlled trial investigating the effect of tank material on growth and survival parameters of Pacific white shrimp. Days correspond to the days that an individual shrimp survived; Event correspond to the Death event, 0 = Survival and 1=Death; Treatment refers to codes for the treatments where 1, 2 and 3 correspond respectively to Fiberglass reinforced plastic, Douglas fir and oak”. 4. Information on statistical analyses conducted, including results of Levene’s test for homogeneity of variance and Shapiro-Wilk test for normality, treatment means ± standard deviations for all key outcome parameters, p-values for ANOVA and post hoc Tukey pairwise comparisons between treatments (for survival rate, weight gain, specific growth rate and feed conversion ratio), and p-values and pairwise comparisons for the Kaplan-Meier survival analysis. Named “Table S4: Statistical summary of survival, growth rate, specific growth rate and feed conversion performance of Pacific white shrimp (PWS) reared in tanks lined with fiberglass reinforced plastic (FRP), Douglas fir, and oak wood”.
Keywords: Penaeus vannamei; Douglas fir wood; oak wood; rearing tank; construction material; sustainability; wood extractives; ddc:570; ddc:590; ddc:630